FUND INDEXES AND ECONOMIC INDICATORS BEHAVIOR AS CRISIS RED FLAGS - Г. А. Мажара; М. О. Сазонова (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut")
Financial crises may happen for different reasons. The most obvious reason is overwhelming the assets or institutions’ prices, which are not supported by anything but market demand. If this situation is topped by anticipated human behavior, government non-interference for a long time or just a “black swan”, the crisis may cause a recession or depression. The main goal of this article is to discover the root causes of the main global crises of the 20th and 21st centuries and to compare them. Preparing the work, the following methods were used: systematic analysis of the scientific literature; comparative analysis; systematization, comparison and summarizing of the results. As a result, aim of this article: to have a look at the global crises of the previous decades, study their causes, explore how the stock global markets indexes behaved, was reached. After analysis of several crisis with several indexes we can say that for future research it is advisable to use the indicator The Global DOW index as an equal-weighted stock index.